EP1208 Enhanced recovery after surgery (ERAS) implementation and outcomes in a UK tertiary gynaecological oncology centre. (1st November 2019) - Myriokefalitaki, E; Smith, M; Winter-Roach, B; Slade, R
Abstract : Introduction/Background: Enhanced Recovery Programmes have been proven to successfully prepare patients undergoing major abdominal surgery for an earlier and safe discharge. Methodology: We are presenting The Christie Gynaecological oncology ERAS programme (pre-operative assessment and rehabilitation to peri-operative and inpatient care to post operative discharge support) Results: Substantial reduction of length of hospital stay without compromising in morbidity, re-admissions or return to theatre and excellent patients´ feedback on satisfaction surveys. Conclusion: ERAS programme is feasible and safe in Gynaecological oncology surgery. It order to succeed, requires a robust programme and collaboration with a vast multidisciplinary team. Disclosure: Nothing to disclose